Ultrasound-assisted extraction conditions optimisation using response surface methodology from Mitragyna speciosa (Korth.) Havil leaves - Zakaria, Fazila; Tan, Jen Kit; Mohd Faudzi, Siti Munirah; Abdul Rahman, Mohd Basyaruddin; Ashari, Siti Efliza (Elsevier, 2021)
The optimisation of the Ultrasound-Assisted Extraction (UAE) method was investigated by employing the Central Composite Rotatable Design (CCRD) of Response Surface Methodology (RSM). The UAE method was based on a simple ultrasound treatment using methanol as the extraction medium to facilitate the cell disruption of Mitragyna speciosa leaves for optimum extraction yield and Total Phenolic Content (TPC). Three different parameters comprising extraction temperature (X1: 25–50 °C), sonication time (X2: 15–50 min), and solvent to solid ratio (X3: 10–30 mL/g), and were selected as the independent variables, while two response variables were selected, namely extraction yield (Y1) and TPC (Y2). Based on the results, the developed quadratic polynomial model correlated with the experimental data is based on the coefficient of determination (R2) of extraction yield (0.9972, p < 0.0001) and TPC (0.9553, p < 0.0001). At 25 °C, 15 min sonication time, and 10 mL/g of solvent to solid ratio, the optimal conditions recorded an extraction yield and TPC of 22.69% and 143.51 mg gallic acid equivalent (GAE)/g, respectively. Furthermore, the actual response and the predicted values of the developed models correlated with each other as the Residual Standard Error (RSE) values were <5%. Meanwhile, the Liquid Chromatography- tandem Mass Spectrometry (LC-MS/MS) was employed to characterise the optimised M. speciosa extract and revealed the presence of major phytochemicals, including catechin, rutin, kaempferol, coumarin, gallic acid, chlorogenic acid, and caffeic acid. These compounds could exhibit certain therapeutic effects, such as anti-inflammatory, antibacterial, and antioxidant. Therefore, the findings in this study supported the suggestion that the various available bioactive compounds besides alkaloids contributed to the bioactive properties in M. speciosa, making it an effective traditional herbal medicine to treat various illnesses.